A Inconstitucionalidade Da Limitacao Para Deducao De Despesas Relacionadas Com Instrucao Da base De Calculo Do Imposto Sobre a Renda (Global Journal of Management and Business Research, 2019)
The present paper has as goal, to demonstrate the unconstitutionality education expenses discounts limitation inside Income Tax base. To motivate the paper, it will be demonstrated that the law that enforces the discounts limitation violates the right to education, the Income Tax rule array of incidence, the ability to pay, equality, fairness and proportionality principles. Will be revealed the contradiction existed between the absence of limitations to other kinds of expenses discounts, while there's a limitation only for education expenses discounts. The case law about the subject and the direct action of unconstitutionality brought to the Brazilian Supreme Court will also be analyzed. By the end of the paper, the unconstitutionality of the law that enforces the education expenses discounts limitation inside Income Tax base will be proved.
Keywords: income tax; tax base; education expenses; discounts limitation unconstitutionality